Zn-Co nanoferrite electrocatalysts for enhanced hydrogen and oxygen generation - Kiran Shahzadi; Muhammad Sarfraz; Muneerah Alomar; M.A. Mujtaba; Muhammad Nasir Bashir; Muhammad Mahmood Ali; Faisal Ali (Results in Chemistry)
This study aims to investigate the role of Zn1-xCoxFe2O4 electrocatalysts in enhancing the efficiency of water splitting reactions for hydrogen and oxygen evolution. A potpourri of hydrothermally synthesized Zn1-xCoxFe2O4 electrocatalysts was prepared to enhance water splitting reaction to evolve valuable hydrogen and oxygen gases. Fourier transform infrared spectroscopy and X-ray diffraction techniques respectively corroborated chemical synthesis and cubic spinel structure of Zn1-xCoxFe2O4 alpha-ferrite electrocatalyst nanocrystals. Electrocatalytic behavior of prepared electrocatalysts was measured in terms of Tafel slope, overpotential and onset potential via linear sweep voltammetry and cyclic voltammetry techniques. Electrochemical impedance spectroscopy assessed electrocatalytic capability for solution resistance and charge transfer. Electrocatalyst with higher concentration of cobalt than zinc in concocted ferrites (CoFe2O4), rendered largest electrocatalytic oxygen evolution reaction with lowest charge transfer resistance of 2.1 Ω, onset potential of 1.51 V, overpotential of 280 mV, and a Tafel slope of 65 mV/dec. Synthesized nanoferrite materials find electrocatalytic potential for evolution of hydrogen and oxygen in water splitting reactions according to electrochemical investigations. The findings suggest that Zn₁₋ₓCoₓFe₂O₄ electrocatalysts, particularly those with higher cobalt content, can serve as efficient electrocatalysts for water splitting, providing a pathway for clean hydrogen fuel production.